Emerging Middle Class in China and Its Unique Culture and Value System - Wu, Fengjiao (2012)
Abstract Purpose The paper aims to identify the middle class in China as in a typical emerging market. This is instrumental for the global businesses that desire to expand the markets, especially those who target the emerging middle class. Design and Methodology The paper offers a definition for middle class in China and also gives three criteria for identifying middle class. Then the questionnaires concerning the culture dimensions of middle class and working class were sent out and collected to find out what demographic factors have influence on the culture value system of different social classes. Findings Among all the six cultural dimensions, the Power distance, Individualism, Masculinity, Long-term orientation and Indulgence versus Restraint are significantly influenced by one or some of the factors of age, gender, education, income, occupation and marital status. Due to the difference of income, education and occupation, the cultural value system is different between working and middle class. This difference allows global businesses to make tailored branding and marketing strategies for emerging middle class in China. Originality and Value Although there are researches and literatures on defining middle class and identifying their role in the emerging market, this is the first time the culture value system being applied to make comparison between working and middle class, thus to inspire the global businesses of marketing and branding strategies.